Erythrina variegata Linn: A review on morphology, phytochemistry, and pharmacological aspects - Kumar, A.; Lingadurai, S.; Jain, A.; Barman, N. R. (Pharmacognosy Reviews)
This review gives an account of the current knowledge on the morphology, phytochemistry, and pharmacological aspects of Erythrina variegata. E. variegata also called Erythrina indica is a thorny deciduous tree growing to 60 feet tall. A wide range of chemical compounds have been isolated, mainly alkaloids, flavonoids, triterpenoids, and lectin. Different parts of the plant have been used in traditional medicine as nervine sedative, collyrium in opthalmia, antiasthmatic, antiepileptic, antiseptic, and as an astringent. The alkaloids extracted from the leaves of E. variegata are reported to have anti-inflammatory and analgesic activity. Isoflavonoids isolated from E. variegata having antibacterial and anthelmintic activity. E. variegata shows several other characteristic pharmacological effects like neuromuscular blocking, smooth muscle relaxant, CNS depressant, and hydrocholeretic, which are consistent with the reported uses of the plant extracts in the indigenous system of medicine. Hence the present article includes the detailed exploration of morphology, phytochemistry, and pharmacological aspects of E. variegata in an attempt to provide a direction for further research.
Keywords: Alkaloids; antibacterial; cytotoxicity; Erythrina variegata; isoflavonoids